Devaney Chaos and Distributional Chaos in the Solution of Certain Partial Differential Equations - Xavier Barrachina; J. Alberto Conejero (Abstract and Applied Analysis)
The notion of distributional chaos has been recently added to the study of the linear dynamics of operators and C0-semigroups of operators. We will study this notion of chaos for some examples of C0-semigroups that are already known to be Devaney chaotic.